Solve first equation for y:
5x+y=10
y=10-5x. Plug this equation into second equation
-x-(10-5x)=-2
-x-10+5x=-2
4x=8
x=2 (plug x into first equation)
5(2)+y=10
y=0
Sample Equation: 3x - 3 = 27
Multiple step:
3x - 3 = 27
<u> + 3 +3</u> Step1. Remove the -3 by adding 3 to both sides
3x = 30
<u>÷3 ÷ 3</u> Step2. Remove the multiplicand 3 by dividing both sides by 3
x = 10
To check: substitute x by its value
3x - 3 = 27
3(10) - 3 = 27
30 - 3 = 27
27 = 27
Answer:
![x=3, y = 49\\x=0.5, y = -3.5\\x=-0.67, y = -2.31](https://tex.z-dn.net/?f=x%3D3%2C%20y%20%3D%2049%5C%5Cx%3D0.5%2C%20y%20%3D%20-3.5%5C%5Cx%3D-0.67%2C%20y%20%3D%20-2.31)
Step-by-step explanation:
![y=6x^2-5\\y=17x-\frac{6}{x}](https://tex.z-dn.net/?f=y%3D6x%5E2-5%5C%5Cy%3D17x-%5Cfrac%7B6%7D%7Bx%7D)
Let's substitute the first equation into the second one.
![6x^2-5=17x-\frac{6}{x}](https://tex.z-dn.net/?f=6x%5E2-5%3D17x-%5Cfrac%7B6%7D%7Bx%7D)
- Multiply by
and bring all the terms to one side.
I'll use my graphical calculator to solve this but you could factor:
(All rounded to 2 decimal places)
Now we can substitute these
values into an equation for
.
![y=6x^2 - 5](https://tex.z-dn.net/?f=y%3D6x%5E2%20-%205)
![x=3, y = 49\\x=0.5, y = -3.5\\x=-0.67, y = -2.31](https://tex.z-dn.net/?f=x%3D3%2C%20y%20%3D%2049%5C%5Cx%3D0.5%2C%20y%20%3D%20-3.5%5C%5Cx%3D-0.67%2C%20y%20%3D%20-2.31)
The researcher exercise direct control over at least one variable.